Being the Bible: Sacred Bodies and Iconic Books in Bring Your Bible to School Day. Issue 1 (24th June 2019) - Parmenter, Dorina
Abstract : Bring Your Bible to School Day has been a rapidly growing annual event in US schools since 2014. It involves a ritual with the processional object, the Bible in its many personalized variations, operating as an icon that invokes the presence of God and legitimizes evangelical Christians who see themselves as the agents of God's return to American schools and society. In this ritual, the Bible also functions to index its possessors as affected biblical bodies, or visible manifestations of God's word. This article analyzes the activities and discourses surrounding Bring Your Bible to School Day in light of material attitudes and practices in Protestant Christianity, including iconoclasm and biblicism, and recent scholarship on iconic books.